Arab Human Development Report 2009 - United Nations Development Programme (United Nations, 2011)
Like the first Arab Human Development Report, this fifth volume in the series undertakes a broad diagnostic of the state of development in Arab countries, this time through the lens of human security. Adopting a more differentiated approach to the particular contours of sub-regions, it shows that the concept of human security offers a relevant framework for refocusing the social contract in the Arab countries on neglected priorities. The Report analyzes interdependent threats and downturns that undermine the safety and development prospects of individuals and states alike, and indicates policy orientations that Arab governments, civil society, citizens and international actors could adopt in response.